2022
DOI: 10.1017/s0960258522000071
|View full text |Cite
|
Sign up to set email alerts
|

Correlated evolution of seed mass and genome size varies among life forms in flowering plants

Abstract: Seeds show important variation as plant regenerative units among species, but their evolutionary co-variations with other plant characteristics are still poorly understood. Whilst a positive association of seed mass with genome size (GS) and life forms has already been documented, a broad-scale quantification of their evolutionary correlation and adaptive selection has never been conducted. Here, we tested for correlated evolution of seed mass and GS towards distinct selective regimes related to life form in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 64 publications
(104 reference statements)
2
21
0
Order By: Relevance
“…This idea is compatible with the 'large-genome-constraint' hypothesis, which postulates that large genomes might be maladaptive (Vinogradov, 2003;Knight et al, 2005). For example, large-genomed plants are restricted to having large seeds (Knight & Ackerly, 2002;Beaulieu et al, 2007;Carta et al, 2022) and stomata (Beaulieu et al, 2008;Veselý et al, 2012) because a larger genome occupies more volume (Cavalier-Smith, 2005). Large seeds and stomata might limit species' dispersal ability (Sonkoly et al, 2017) and narrow their ecological niche, as large stomata are detrimental in drier conditions (Veselý et al, 2020), leading to smaller geographical ranges (Sheth et al, 2020).…”
Section: Support For the Mhh: Genome Size And Range Size Are Inversel...mentioning
confidence: 72%
“…This idea is compatible with the 'large-genome-constraint' hypothesis, which postulates that large genomes might be maladaptive (Vinogradov, 2003;Knight et al, 2005). For example, large-genomed plants are restricted to having large seeds (Knight & Ackerly, 2002;Beaulieu et al, 2007;Carta et al, 2022) and stomata (Beaulieu et al, 2008;Veselý et al, 2012) because a larger genome occupies more volume (Cavalier-Smith, 2005). Large seeds and stomata might limit species' dispersal ability (Sonkoly et al, 2017) and narrow their ecological niche, as large stomata are detrimental in drier conditions (Veselý et al, 2020), leading to smaller geographical ranges (Sheth et al, 2020).…”
Section: Support For the Mhh: Genome Size And Range Size Are Inversel...mentioning
confidence: 72%
“…Leitch, Chase, and Bennett 1998; Bennet and Ilia J. Leitch 2005; Puttick, Clark, and Donoghue 2015; Carta et al 2022).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Meagher et al [ 18 ] found that DNA content was again negatively correlated with flower size. Angelino et al [ 19 ] indicated a positive correlation between genomic C-value and seed quality in angiosperms. Korban et al [ 20 ] determined the genomic C-value of 100 apple germplasm and showed that genomic C-value and stomatal length were positively correlated.…”
Section: Introductionmentioning
confidence: 99%